Analisis Akar Permasalahan Keterlambatan Penyerahan Dokumen Pembelian pada Masa Onboarding di Divisi Pengadaan PT. X - Santi, Erlina; Dai, R. Ratna Meisa; Hakim, Raden Marsha Aulia (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2025)
This study analyzes the root causes of delays in submitting Purchase Order (PO) documents to suppliers during the onboarding period for new employees in the Procurement Division of PT. X. This problem impacts the smoothness of the company's supply chain and production operations, namely the purchasing process. In the purchasing process, problems occur at the final stage of submitting purchasing documents to suppliers, experiencing delays. This delay reached 59.8% during the onboarding period. Using a descriptive qualitative approach, data was obtained through in-depth interviews, non-participatory observation, and documentation studies. The analysis was conducted using a Fishbone diagram based on the 6M categories (manpower, method, machine, material, measurement, environment). The results show that the dominant factors causing delays are a lack of understanding of the e-procurement system by new employees, data input errors, excessive workloads for existing employees, unsystematic training methods, the absence of written work instructions, and limited communication in the hybrid work model. Proposed solutions include providing written training modules to accompany learning, post-training evaluations to measure job readiness, and improving the onboarding flow to make it more efficient. The implementation of this solution is expected to minimize delays in PO documents and increase the effectiveness of the procurement process.